Study of Sign in The Naruto Film: A Semiotic Analysis - Helmita Helmita; Rhezy Hasila Diandri (Jurnal Ilmiah Langue and Parole, 2025)
This research aims to explore in depth the use of signs in the Naruto film through a semiotic perspective. The researcher used a qualitative research method with a descriptive approach, which allows for in depth analysis of the meaning contained in each visual and verbal element. Data were obtained from various key scenes, dialogues between characters, and visual elements that are significantly relevant to the storyline. Through systematic data collection, this study focuses on how these signs are used to shape the narrative and convey specific messages in the Naruto film. The analysis process was conducted with reference to the semiotic theory of Charles Sanders Peirce and Roland Barthes. Peirce's theory is used to identify signs in the form of icons, indexes, and symbols, while Barthes' theory is used to interpret the meaning of signs through three levels, namely denotation, connotation, and myth. The results of the study revealed that the signs found not only have basic meanings according to the context of the story, but also contain cultural and moral messages. These layered meanings play an important role in enriching the story, building an emotional atmosphere, and conveying cultural values to the audience. Thus, this research confirms that semiotic studies are an effective approach to understanding the multimodal communication that occurs in Naruto, especially in relation to the delivery of moral messages and cultural values.